2008
DOI: 10.1371/journal.pone.0002461
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from M. Bovis BCG Infected Macrophages Activate Antigen-Specific CD4+ and CD8+ T Cells In Vitro and In Vivo

Abstract: Activation of both CD4+ and CD8+ T cells is required for an effective immune response to an M. tuberculosis infection. However, infected macrophages are poor antigen presenting cells and may be spatially separated from recruited T cells, thus limiting antigen presentation within a granuloma. Our previous studies showed that infected macrophages release from cells small membrane-bound vesicles called exosomes which contain mycobacterial lipid components and showed that these exosomes could stimulate a pro-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(202 citation statements)
references
References 40 publications
(49 reference statements)
6
193
0
3
Order By: Relevance
“…For example, EVs derived from Mycobacterium bovis Bacillus Calmette Guérin-infected macrophages promote T cell immunity in mice in the presence of DCs, whereas EVs from Toxoplasma gondii-pulsed DCs can confer protection against parasite infection in mice (33)(34)(35). EVs from CMV-infected epithelial cells stimulate memory CD4 + T cells in a DC-dependent manner.…”
Section: Immune Regulation By Antigen-presenting Cell Evsmentioning
confidence: 99%
“…For example, EVs derived from Mycobacterium bovis Bacillus Calmette Guérin-infected macrophages promote T cell immunity in mice in the presence of DCs, whereas EVs from Toxoplasma gondii-pulsed DCs can confer protection against parasite infection in mice (33)(34)(35). EVs from CMV-infected epithelial cells stimulate memory CD4 + T cells in a DC-dependent manner.…”
Section: Immune Regulation By Antigen-presenting Cell Evsmentioning
confidence: 99%
“…[93][94][95][96][97][98][99] Exosomes are small nanometer-sized (50-100 nm) vesicles of endocytic origin, which are released in the extracellular milieu by several cell types. [100][101][102][103][104][105][106][107][108][109] Previous studies have shown the intriguing role of exosomes in tumor progression because of the ability of tumor cell-derived exosomes to modulate and mold the host microenvironment, thereby promoting tumor cell growth and disease progression. [110][111][112][113] Although preparation of the premetastatic niche has not been studied in MM, we recently showed in preliminary data that stromal cells present in contact with MM cells secrete exosomes that modulate the growth and dissemination potential of MM cells.…”
Section: Micrometastasis and The Premetastatic Nichementioning
confidence: 99%
“…Notably, exosomes derived from macrophages infected with an intracellular pathogen, such as Mycobacterium tuberculosis or Mycobacterium bovis, shed exosomes that are transmitted to distant DCs, leading to presentation of pathogenspecific antigens to CD4 + T cells and DC maturation. Similarly, exosomes derived from endothelial cells infected with cytomegalovirus (CMV) convey CMV-specific antigens to DCs to activate CD4 + T cells (Giri and Schorey, 2008;Walker et al, 2009).…”
Section: Physiological (Immunological) Roles Of Exosomesmentioning
confidence: 99%